CALCULATION OF INSURANCE PREMIUMS FOR AGRICULTURAL RISKS IN RA - Gulyan, Anahit (Bulletin of Yerevan University G: Economics, 2020)
The present article discusses the necessity of agricultural risk insurance in the territory of the Republic of Armenia. The main result of the article is the calculation of premium for agricultural risk insurance. The calculation was done through actuarial and profitability index methods. The impact of the application of insurance premium on the incomes of the farmers was also touched upon in the work.
Keywords: agricultural risks, insurance, insurance premium, profitability index, insurance tariff, risk management, compensation